Agile Development of a Patient Feedback System for Continuous Improvement of Neurology Clinic Services - Sihombing, Denny Jean Cross (Jurnal Ekonomi, 2024)
This research addresses the problem of insufficiently adaptive and re-sponsive patient feedback systems in neurology clinics, which can hinder service quality improvement. The methods employed include user needs analysis, application development using an agile approach, user acceptance evaluation, and continuous improvement based on feedback. The research findings indicate that implementing a respon-sive and integrative patient feedback system can enhance patient satis-faction, clinic process efficiency, and overall service quality. This re-search contributes to providing a framework that can be applied to de-velop effective and adaptive patient feedback systems in the context of healthcare services, with the potential to enhance patient experience and operational efficiency in neurology clinics.